Investigating the role of R2TP-like co-chaperone complexes during axonemal dynein assembly - Lennon, Jennifer (The University of Edinburgh, 2022)
Motile cilia are specialised cell-types which in humans have important roles in the linings of the airways, the reproductive system and the brain. The movement, required for this type of cilia to function, is facilitated by structures called axonemal dynein motor complexes. These are large, multi-subunit structures, and so it is crucial that they are assembled correctly. In humans, if the motility of these is defective, it can lead to a disorder called Primary Ciliary Dyskinesia, or PCD. This is a heterogeneous, autosomal recessive disorder – symptoms of which include abnormally positioned organs, chronic respiratory infections and infertility. Therefore, the development and structure of the motile cilia is tightly regulated by multiple proteins including chaperones, dynein axonemal assembly factors (DNAAFs), microtubule inner proteins (MIPs), the outer arm docking complex (ODA-DC) and the nexin-dynein regulatory complex (N-DRC). Chaperones work with co-chaperones to regulate their many functions within the cell. One of these co-chaperones is the R2TP complex, which was originally discovered in yeast but is conserved in higher organisms. This multi-protein co-chaperone is involved in the assembly of multi-subunit complexes such as the axonemal dynein motors. Two of the R2TP subunits, Pontin and Reptin, are involved in many cellular functions both in this co-chaperone complex and independently. It is thought that as some DNAAFs share similar protein domains to the components of the R2TP complex, they may form R2TP-like complexes. However, the specific details surrounding the roles of these complexes during the assembly process remains unclear. The structure of motile cilia is highly conserved throughout evolution and Drosophila melanogaster has been shown previously to be an excellent model for furthering understanding into the development and function of these structures as only two cell types in the fly contain axonemal dynein motor complexes. These are the chordotonal neuron, which has a motile ciliated dendrite essential for its mechanosensory function, and the sperm flagellum. In this thesis, I use the Drosophila model to further characterise putative ciliary genes (Wdr16 and Dpcd) identified by a transcriptome analysis previously carried out in the lab. RNAi knockdown experiments as well as expression analysis supported motile cilia functions. The diversity which has been identified regarding the roles of these two putative ciliary genes highlights how proteins can be involved in motile cilia in different ways. I also use this genetically tractable model to further understand the roles of the individual proteins of a previously identified R2TP-like complex (R2DP3). Electron microscopy, proteomics and investigation into how the localisation of dynein subsets was affected in null mutants (generated using CRISPR/Cas9) allowed for the role of this R2TP-like complex in the dynein assembly process to be further specified. Using co-immunoprecipitation and affinity purification, we identified an additional protein complex featuring Pontin and Reptin of the R2TP complex, alongside the DNAAF Heatr2 and the putative DNAAF Dpcd. As well as a role in dynein assembly, both DNAAFs are additionally expressed in the neuroblasts of the CNS, and disruption to their function results in a late larval lethality. Therefore, we have found these genes to not be specific to the dynein assembly process and hypothesise that Dpcd may have an additional function (working with Pontin, Reptin and potentially Heatr2) in the regulation of AKT signalling and therefore impact cell proliferation.
Keywords: Motile cilia; Primary Ciliary Dyskinesia; PCD; dynein axonemal assembly factors; DNAAF; Drosophila